GAYA BAHASA DALAM NOVEL TEENLIT TRILOGI “D’ANGEL”KARYA LUNA TORASHYNGU - Amelia Rosalina; Suryadi Suryadi; Irma Diani (Jurnal Korpus, 2018)
The purpose of this study is to describe the quality of the language available in the novel teenager "D'Angel Princess" by Luna Torashyngu. The method used in this research is descriptive qualitative method. Data in this study Various styles on the novel teenagers "D'Angel Princess" by Luna Torashyngu. Documentation technique is used in the data collection technigue. Data analysis technique in this research is done through steps, that is: (1) reading novelteenlit "Angel Angel" by Luna Torashyngu (2) hiding data, (3) classifying data, (4) analyzing data, and (5) conclude. Test the validity of the data is a credibility test conducted by increasing persistence with the supervisor during the process, and discussion with colleagues. The results found in the novel D'Angel Princess by Luna Torashyngu in slang and not used to separate the characteristics of the teen novel. Then the word denotation and author connotation to express and convince the compiler readers convey narration and description in the story, said Science used as a means to monetize a novel theme with a scientific theme, the words used to sort out teenage characters who look slang. The use of sentences is used to describe the main character in the sentence Usage. The author's written sentence contains descriptions and narrations to make the story more interesting and easy to understand. Comment topic sentence  gives a beautiful impression or a beautiful comment on the characters. Use of minor sentences is used  to give challenge and sincerity to what people say so that readers feel confidence. Minor sentences and reciprocal is used by writers when delivering narration in serious situations or moods.Keywords: language style, teenlit novel, "D'Anggel" by Luna Torashyngu